Central Serous Chorioretinopathy - Chhablani, Jay (Academic Press, 2019)
Central Serous Chorioretinopathy discusses the mechanisms, pathogenesis and risk factors of CSCR, findings on various imaging modalities, available treatment options, and translational research into new treatment options for CSCR management. This comprehensive book is written for retina specialists and surgeons, researchers and clinical practitioners in sensory systems (vision), and ophthalmologists. Central Serous Chorioretinopathy (CSCR) is a common disorder across the world with a variable prognosis without any standard of care. Recently, advancements in imaging have led to a better understanding of the pathogenesis and mechanisms of this disease.